The Democratization of educational inequalities in France and the United Kingdom: A Global Update, a Local Reading - Luzon, Antonio; Torres, Mónica (Education Policy Analysis Archives, 2006)
This article uses a comparative perspective to analyze English and French educational policies focused on equal opportunity. Specifically. the British Education Action Zones and the French Zones d’Action Prioritaire. Although these two educational policies are different applied in two distinctive social and political contexts, both cases are showing convergence in their understanding of the concept of equal opportunity. This convergence indicates that these policies are the product of processes of hybridization between national and global tendencies.